The Analysis of the Effect of Halal Logistics Attributes and Service Quality on Halal Logistics Adoption Intention Through Emotional and Functional Values - Arief, Syaeful; Aji, Taufiq; Kristanto, Dwi; Dwijayanti, Khusna; Prasetyo, Eko Heru (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract This study aims to analyze the effect of halal logistics attributes and service quality on halal logistics adoption intention, by considering the mediating role of emotional value and functional value. An explanatory quantitative approach is used through the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, with data obtained from 200 respondents who have used halal logistics services in Indonesia in the last six months. The results show that service quality has a significant effect on emotional value (β = 0.655; p < 0.001) and functional value (β = 0.458; p < 0.001). Halal logistics attributes also have a significant influence on emotional value (β = 0.168; p = 0.001), but not directly on adoption intention. Emotional value (β = 0.378; p < 0.001) and functional value (β = 0.461; p < 0.001) proved to be important mediators that bridge the influence of exogenous variables on halal logistics adoption intention. Overall, the model has an R² value of 0.422 for the adoption intention variable, indicating that the model is able to explain 42.2% of the variability in adoption intention. These results underscore the crucial role of perceived emotional and functional value in influencing consumers' decision to adopt halal logistics services. Keywords: halal logistics, service quality, emotional value, functional value, adoption intention, SEM-PLS